„Euthymia” we fragmentach Demokryta z Abdery - Narecki, Krzysztof (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The author carries out a thorough philological analysis of 9 fragments of Democritus, in which both the noun εὐθυμίη and related verbs and adjectives appear. This allows to establish the contextual semantic scope of the basic concept and to define the role it plays in Democritus’ ethical thought.